Entrepreneurial innovation : strategy and competition aspects - Ratten, Vanessa (Studies on entrepreneurship, structural change and industrial dynamics, 2022)
This book explores and asserts that there are many different types of innovation but in order to bring about fundamental change to society the innovation must be entrepreneurial. The aim of this edited book is to focus on different elements of entrepreneurial innovation in order to understand emerging issues and trends. This book shows how this enables an increase in research attention placed on how entrepreneurial innovation must have a strategic intent in order to facilitate societal change. The role of competition in enabling organizations to utilise innovation that is cutting edge is discussed with the goal of bringing together the disparate literature on entrepreneurship and innovation in terms of international competitiveness. This book presents at length examinations on how entrepreneurship can facilitate healthier strategy and competition in organisations and beyond.